Synchronisation cost of multi-controller deployments in software-defined networks. (2016) - Benamrane, Fouad; Ros, Francisco J.; Mamoun, Mouad Ben
The logically centralised control plane in software-defined networks (SDN) must be physically distributed among multiple controllers for performance, scalability and fault tolerance reasons. However, this means that the network state must be synchronised among the different controllers to provide control applications with a consistent network view. In this paper, we explore such synchronisation cost in a widespread SDN controller platform by emulating real wide-area network topologies. Our results show that the synchronisation delay is lower than typical restoration times in currently deployed networks, showing the feasibility of multi-controller deployments from a network latency viewpoint. For this, the controllers make use of a substantial amount of bandwidth that might be traded-off for synchronisation delay when the deployment scenario allows it.